Estudio epidemiológico e impacto psicosocial del abuso de sustancias psicotrópicas en estudiantes de Enfermería de la Universidad Nacional de Loja - Mora Huiracocha, Danny Renato (2022)
Psychotropic substances are those that act on the central nervous system, producing neurophysiological effects and affecting mental processes, which affect the person who directly consuming and their family nucleus, both in behavioral, physical and mental changes, academic failure, family disintegration and even traffic accidents. This investigative work was contextualized in students of the nursing career from the Universidad Nacional de Loja, with the objective of evaluating the epidemiological profile and the psychosocial impact of the abuse of psychotropic substances. For which a descriptive study was carried out, with a quantitative approach, observational type, correlational cross-sectional cohort, a type of simple random sampling, obtaining a total of 140 students out of 217, carefully analyzing the responses obtained through the application of the questionnaire of CRAFFT. All the data were systematized and analyzed in Excel. The obtained results showed that 72.86% of the students were female, 55% corresponding to ages 20 to 22, 80% of them live with their family, with an average consumption age of 42.86%. in 15 to 17 years, with alcohol being the most consumed at 55%, followed by tobacco at 10% and 8.57% marijuana. It is concluded that most of the students in this study presented a high consumption of alcohol, followed by tobacco and marijuana. Additionally, sex, age, marital status and economic situation do not have a statistically significant relationship, in addition to students who are from the urban area